Seroreactivity against MAGE-A and LAGE-1 proteins in melanoma patients - Usener, Dirk; Gerhardt, A.; Schadendorf, Dirk; Eichmüller, Stefan B. (British journal of dermatology, 2003)
Background: Cancer-testis antigens exemplify a growing number of tumour antigens which are expressed in a variety of malignancies, but not in normal tissues other than germ cells, primarily those of the testis. Objectives: To investigate the humoral response to known cancer-testis antigens in melanoma patients. Methods We used phage clones coding for seven different melanoma antigens MAGE-A or LAGE-1A proteins. These clones were isolated using the newly developed DNA hybridization analysis of recombinantly expressed cDNA libraries (HYREX) approach. HYREX combines the advantage of a nonradioactive library screening method with the possibility of subsequently analysing the serological response to the recombinant proteins. We isolated clones coding for MAGE-A1, -A3, -A4b, -A6, -A9 and -A12, as well as LAGE-1A. Additionally, we correlated gene expression and seroreactivity. Results: Between 13% and 27% of sera (n = 15) were reactive against individual tumour antigens. We found the presence of specific antibodies was, with only two exceptions, generally correlated with mRNA expression of the antigen within cell lines derived from the same patient. While cross-reactivity of patients' IgG might play a role in these cases, antibodies from patients' sera were able to distinguish even the closely related MAGE-A3 and -A6. In general, the mRNA expression frequency was higher than the detected IgG responses. Conclusions: Antibody recognition of specific tumour antigens by patients' sera may be used for evaluating the possible immunogenicity of new antigens; serological tests could be used for tumour monitoring purposes.
Gesehen am 23.11.2020